Determining the content validity and reliability of twed matrix as a cognitive debiasing strategy in clinical decision making in Emergency Department - Saad, Mohd Shukri Mat (2017)
Background: Cognitive biases always complicate clinical decision making in emergency department. TWED Matrix was invented as a tool for debiasing strategy to reduce diagnostic error caused by cognitive biases. It is in the form of mnemonic to encourage metacognition by doctors to reduce errors in clinical decision making in emergency department. As it is relatively new tool, a study was conducted to determine the content validity and reliability of TWED Matrix as cognitive debiasing strategy in clinical decision making in emergency medicine. Methodology: This study was divided into two stages; the developmental stage and the judgment stage. In the developmental stage, we narrowed down 50 cognitive biases into six classes, and total of four vital questions covering eight items were asked. Then, in the judgment stage, emergency physicians as expert judges were chosen to evaluate eight items in the form of Likert scale for their relevance and representativeness. For relevance, CVI and modified Kappa were assessed and for representativeness, CVI was calculated. Reliability was tested using Cronbach Alpha. Results: For relevancy, all of the items were scored of CVI more than 0.78. CVI average for relevancy was 0.89. Modified Kappa statistic was calculated to make adjustment for possibilities of chance agreement. For representativeness, all eight items produced CVI of more than 0.78 which is the minimum value for CVI acceptance. CVIaverage was 0.94. Alpha value for item relevancy was 0.767 which is within acceptable value. Reliability on item representativeness produced Cronbach’s Alpha of 0.737 which is still above acceptance value of 0.7. Conclusion: TWED Matrix showed significant validity and reliability in this study although further evaluation and assessment needed to strengthen the power of the study before it could safely and widely use as a cognitive debiasing strategy in clinical decision making in emergency department.